John von Neumann's game-theoretic legacy - András Simonovits (Hungarian Academy of Sciences, Institute of Economics, Centre for Economic and Regional Studies, 2024)
John von Neumann (Budapest, 1903-Washington D.C., 1957) was an exceptional polymath, who made fundamental contributions to mathematical logics, functional analysis, quantum mechanics, game theory, computer architecture and automata theory. In this brief paper, I shall review the game-theoretic results of von Neumann and their legacy in an informal way.
Keywords: B16; C7; 330; game theory